Science Support for Climate Change Adaptation in South Florida - Laura M. Early; Rebecca G. Harvey; Laura A. Brandt; James I. Watling; Frank J. Mazzotti (EDIS, 2010)
WEC286, a 5-page illustrated fact sheet by Laura M. Early, Rebecca G. Harvey, Laura A. Brandt, James I. Watling, and Frank J. Mazzotti, discusses how climate change will affect sea level and the ecosystem in South Florida and outlines the Department of Interior’s approach to manage public lands and natural resources impacted by climate change. Includes references. Published by the UF Department of Wildlife Ecology and Conservation, July 2010.